FACTORS AFFECTING PROFIT MANAGEMENT IN THE HEALTHCARE SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE - Ilham, Gery; Daryatno, Andreas Bambang (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to examine the effect of Audit Opinion, Size of Public Accounting Firm (KAP), Profitability and Leverage on Earnings Management of a company. This research was conducted using secondary data. The population in this study were healthcare companies listed on the Indonesia Stock Exchange in 2020 - 2022. The research method used in this research is multiple regression analysis with sampling using purposive sampling method. The selected samples from 3 periods were 63 samples, which will then be used as research material. The results of this study indicate that the profitability variable has a significant positive effect on the earnings management of a company, while the audit opinion variable, the size of the public accounting firm (KAP) and leverage have no significant effect on the earnings management of a company. The Adjusted R Square value is 0.110, this means that 11.00% of the dependent variable can be explained by the independent variable, while the remaining 89.00% is explained by other variables outside the model.